Alterations in vasopressin regulation in Alzheimer's disease. Issue 7 (July 1988) - Norbiato, G; Bevilacqua, M; Carella, F; Chebat, E; Raggi, U; Bertora, P; Grassi, M P; Mangoni, A
Abstract : A decreased concentration of vasopressin (AVP) in the plasma of patients with Alzheimer's disease has been shown recently and suggests damage to hypothalamic neurosecretory cells. To verify this, osmolar and hypotension (sodium nitroprusside) stimulations on AVP release were applied. The effect of metoclopramide, a powerful stimulator of AVP, was also assessed. Patients with Alzheimer's disease released AVP normally after hypotension. However, AVP response to osmotic stimulation was altered in eight out of 10 patients, owing to low osmoreceptor sensitivity and/or high threshold. Metoclopramide increased AVP in controls but not in patients. Normal AVP response to hypotension in patients with Alzheimer's disease makes it unlikely that there is a significant anatomical loss or damage of hypothalamic neurosecretory cells. Alterations in osmoreceptor function and AVP unresponsiveness to metoclopramide point to damage in the control of AVP release in Alzheimer's disease.